Analisis Yuridis Pemutusan Hubungan Kerja (PHK) Tanpa Pesangon dalam Perspektif Peraturan Pemerintah Nomor 35 Tahun 2021 - Sulthan Fadhil Hisyam (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This research provides a rigorous examination of the termination of employment policies that exempt employers from severance pay obligations under Government Regulation Number 35 of 2021. Within the framework of labor market liberalization introduced by the Job Creation Law, significant legal ambiguity has surfaced concerning the "urgent misconduct" criteria used to disqualify workers from receiving post-employment benefits. Employing a doctrinal legal research methodology with a focus on statutory interpretation and conceptual frameworks, this study investigates the repercussions of these norms on the constitutional safeguards for employees. The analysis reveals that the lack of an independent evidentiary process for verifying grave misconduct creates substantial opportunities for administrative malpractice and unilateral decision-making by employers. Consequently, this shift undermines the principles of social justice and legal certainty, transforming severance pay—originally designed as an economic safety net—into a punitive tool. The study concludes that rigid standardization of misconduct definitions and enhanced labor oversight are imperative to ensure that industrial competitiveness does not compromise the fundamental normative rights of the workforce.